THE IMPACT OF CONFORMATIONAL CHANGES IN ALBUMIN MOLECULE (BSA) ON THE SPECTRAL PROPERTIES OF SQUARAINE AND DICYANOMETHYLENE SQUARAINE DYES - I. V. Hovor; O. M. Obukhova; A. L. Tatarets; O. S. Kolosova; L. D. Patsenker (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2018)
The work was to develop a highly sensitive, fluorescence based method to monitor conformational changes in proteins. With this aim, the influence of unfolding of bovine serum albumin (BSA) molecules on the spectral properties of squaraine dye Sq1 and dicyanomethylene squaraine dye Sq2 was investigated. The conformational changes were initiated by urea in the concentration of up to 8 M. The following three intensity-based methods of using these dyes were evaluated: (i) dye Sq1 was covalently bound to BSA; (ii) dye Sq1 was noncovalently bound to BSA; and (iii) dye Sq2 was noncovalently bound to BSA. The change in the fluorescence intensity of these dyes upon the BSA unfolding was measured. An additional, fourth method was based on the measurements of the change in the Förster Resonance Energy Transfer (FRET) between Sq1 (donor) covalently bound to BSA and Sq2 (acceptor) able to noncovalent binding with BSA. The change in the FRET was due to the BSA unfolding initiated by urea. The absorption and emission maxima measured in water were 635 / 645 nm for dye Sq1 and 654 / 670 nm for Sq2. Addition of 7–8 M urea to aqueous solutions of dyes Sq1 and Sq2 increased their fluorescence intensities by factor of 1.5 and 2.3 while the quantum yield increased by factor of 1.8 and 1.9, respectively. The absorption intensity of Sq1 in the presence of urea had a tendency to decrease while for Sq2 it increased by factor of 1.3. The formation of complexes of dyes Sq1 and Sq2 with BSA as well as the covalent conjugation of Sq1 with BSA caused the red-shift in the absorption and emission maxima and an increase in the quantum yields. Unfolding of BSA molecule resulted in a blue-shift of the absorption and emission bands and a 3-fold decrease in the fluorescence intensity of Sq2–BSA complex. Unfolding of protein in Sq1–BSA conjugate had almost no effect on the position and shape of the absorption and emission bands but decreased the fluorescence intensity by about 20%. At the same time, according to the fourth method the efficiency of FRET from Sq1 conjugated with BSA, to non-conjugated Sq2 exhibited much more pronounced decrease (~10 times) upon BSA unfolding. Thus, the FRET based approach was found to be more sensitive compared to the intensity based methods and therefore can changes in BSA.